TINJAUAN KONSEP IMAGO DEI IRENAEUS DAN THOMAS DARI PERSPEKTIF YOHANES CALVIN SERTA DAMPAKNYA BAGI ZAMAN PASCA MILLENIAL - Hutahaean, Tumpal (STT Reformed Injili Internasional, 2018)
This article seeks to express the uniqueness of John Calvin's understanding of the meaning of Imago Dei as his reaction to the understanding of the theologians of Irenaeus and Medieval Scholastic Aquinas, then to explain the implications of Imago Dei theologically in the context of God's creation along with its significance on self-identity in the digital age. Calvin restores Imago Dei's view back to the bible. His thesis is human must have the right knowledge about God and himself. It is only through Jesus Christ and His word can a man be renewed and knows himself as Imago Dei, so that he can glorify God again. And it is only through the work of the Holy Spirit can man reflects God in this world. KEYWORDS: Imago Dei; total depravity; redemption; renewal; knowing oneself.